A new subgenus and three new species of oribatid mites of the genus Yoshiobodes (Acari, Oribatida, Carabodidae) from Vietnam - Ermilov, Sergey G.; Shtanchaeva, Umukusum Ya.; Subías, Luis S.; Anichkin, Alexander E. (Zootaxa, 2014)
A new subgenus and three new species of oribatid mites of the genus Yoshiobodes, Yoshiobodes (Dongnaiobodes) subgen. nov., Y. (D.) hexasetosus sp. nov., Y. (D.) biconcavus sp. nov. and Y. (Yoshiobodes) neotrichorostralis sp. nov., are described from southern Vietnam. Yoshiobodes (Dongnaiobodes) subgen. nov. differs from the other subgenera, Yoshiobodes (Yoshiobodes) and Yoshiobodes (Berndobodes), by the presence of five to six pairs of genital setae (versus four). Yoshiobodes (D.) hexasetosus sp. nov. differs from Yoshiobodes (D.) biconcavus sp. nov. by the absence of two large concavities in humeral regions of the notogaster and the presence of short, clavate sensilli (versus concavities well developed, sensilli long, thickened, setiform). Yoshiobodes (Y.) neotrichorostralis sp. nov. differs from the other species of the subgenus by the presence of three additional pairs of setae on the lateral sides of the rostrum and the foveolate ornamentation on the notogaster (versus additional setae absent, surface tuberculate). The new generic diagnosis and an identification key to all known species of Yoshiobodes are given. Yoshiobodes ornatus Mahunka, 1987 is proposed as “nomen nudum”. Austrocarabodes (Austrocarabodes) polytrichus Balogh & Mahunka, 1978 combined in the subgenus Austrocarabodes (Uluguroides): A. (U.) polytrichus comb. nov..